Penerapan Model Pembelajaran Cooperative Integrated Reading and Composition Pada Pembelajaran Matematika - Rahmah, Fathatur; Lusiana, Lusiana; Jayanti, Jayanti (Universitas Muhammadiyah Palembang, 2019)
This study aims to determine the effectiveness of the application of the model ofintegrated reading and composition cooperative in students of SMP 44 Palembang in terms of three aspects: student activity during learning, student attitudes to learning, and student learning completeness after being applied in an integrated cooperative reading and composition model. This research is applied research using Pre-Experimental design, One-Shot Case Study. The subjects in this study were class VIII.7 students at SMP Negeri 44 Palembang in the academic year 2018/2019. The instruments used in this study were observation sheets, description test sheets, namely student learning outcomes tests, and student attitude questionnaire sheets on the CIRC learning model. Based on the results of the research and discussion, it was concluded that the effectiveness of the application of the CIRC model on mathematics learning at SMP Negeri 44 Palembang in terms of three aspects of student activity, student attitudes, and student mastery was obtained by KPM (Effectiveness of Model Use) 80% with the category